2022
DOI: 10.1002/bip.23525
|View full text |Cite
|
Sign up to set email alerts
|

Energetically unfavorable protein angles: Exploration of a conserved dihedral angle in triosephosphate isomerase

Abstract: Over the past 3.5 billion years of evolution, enzymes have adopted a myriad of conformations to suit life on earth. However, torsional angles of proteins have settled into limited zones of energetically favorable dihedrals observed in Ramachandran plots. Areas outside said zones are believed to be disallowed to all amino acids, except glycine, due to steric hindrance. Triosephosphate isomerase (TIM), a homodimer with a catalytic rate approaching the diffusion limit, contains an active site lysine residue (K13)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 38 publications
(66 reference statements)
2
8
0
Order By: Relevance
“…Only the N11A variant showed no detectable activity, consistent with the conclusion that the N11–K13 interaction plays an important role in maintaining the unusual K13 Φ dihedral angle. The results of molecular dynamics simulations on these four alanine variants, using PDB ID 2JK2 as the starting structure for Hs TIM, showed that the Φ dihedral angle for K13 was maintained for the M14A, Q65A, and E97A variants but is lost during equilibration of the N11A variant . It was concluded that the change in K13 Φ dihedral angle was responsible for the loss of catalytic activity for the N11A variant.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Only the N11A variant showed no detectable activity, consistent with the conclusion that the N11–K13 interaction plays an important role in maintaining the unusual K13 Φ dihedral angle. The results of molecular dynamics simulations on these four alanine variants, using PDB ID 2JK2 as the starting structure for Hs TIM, showed that the Φ dihedral angle for K13 was maintained for the M14A, Q65A, and E97A variants but is lost during equilibration of the N11A variant . It was concluded that the change in K13 Φ dihedral angle was responsible for the loss of catalytic activity for the N11A variant.…”
Section: Discussionsupporting
confidence: 82%
“…We therefore propose that the effect of the N11A substitution on dimer stability is the result of the perturbation of an extended network of active site hydrogen bonds that includes the N11, K13, Q65, E97, and T75′ side chains and the backbone amide from G′76 (Figure A). We propose that a disruption of this hydrogen-bonded network at the N11A variant of Tbb TIM and Lm TIM results in a large change in the preferred Φ dihedral angle for K13, as was previously proposed to occur for the N11A variant of Hs TIM …”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations